From Wikipedia, the free encyclopedia
Probability Theory
In probability theory, the law of rare events or Poisson limit theorem states that the Poisson distribution may be used as an approximation to the binomial distribution, under certain conditions.[1] The theorem was named after Siméon Denis Poisson (1781–1840). A generalization of this theorem is Le Cam's theorem.
Let
be a sequence of real numbers in
such that the sequence
converges to a finite limit
. Then:
![{\displaystyle \lim _{n\to \infty }{n \choose k}p_{n}^{k}(1-p_{n})^{n-k}=e^{-\lambda }{\frac {\lambda ^{k}}{k!}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/8a2a3853c310482f84dda7f07f5f99f308e75bcc)
Assume
(the case
is easier). Then
![{\displaystyle {\begin{aligned}\lim \limits _{n\rightarrow \infty }{n \choose k}p_{n}^{k}(1-p_{n})^{n-k}&=\lim _{n\to \infty }{\frac {n(n-1)(n-2)\dots (n-k+1)}{k!}}\left({\frac {\lambda }{n}}(1+o(1))\right)^{k}\left(1-{\frac {\lambda }{n}}(1+o(1))\right)^{n-k}\\&=\lim _{n\to \infty }{\frac {n^{k}+O\left(n^{k-1}\right)}{k!}}{\frac {\lambda ^{k}}{n^{k}}}\left(1-{\frac {\lambda }{n}}(1+o(1))\right)^{n}\left(1-{\frac {\lambda }{n}}(1+o(1))\right)^{-k}\\&=\lim _{n\to \infty }{\frac {\lambda ^{k}}{k!}}\left(1-{\frac {\lambda }{n}}(1+o(1))\right)^{n}.\end{aligned}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/1518f1736f85db472179647d5d26e3a8f1587a7a)
Since
![{\displaystyle \lim _{n\to \infty }\left(1-{\frac {\lambda }{n}}(1+o(1))\right)^{n}=e^{-\lambda }}](https://wikimedia.org/api/rest_v1/media/math/render/svg/ff0b32369761856482d7fc00fc8000cca19d3b66)
this leaves
![{\displaystyle {n \choose k}p^{k}(1-p)^{n-k}\simeq {\frac {\lambda ^{k}e^{-\lambda }}{k!}}.}](https://wikimedia.org/api/rest_v1/media/math/render/svg/df85d961c4cf7b4b795a9f3aa72ff850963c7c80)
Using Stirling's approximation, it can be written:
![{\displaystyle {\begin{aligned}{n \choose k}p^{k}(1-p)^{n-k}&={\frac {n!}{(n-k)!k!}}p^{k}(1-p)^{n-k}\\&\simeq {\frac {{\sqrt {2\pi n}}\left({\frac {n}{e}}\right)^{n}}{{\sqrt {2\pi \left(n-k\right)}}\left({\frac {n-k}{e}}\right)^{n-k}k!}}p^{k}(1-p)^{n-k}\\&={\sqrt {\frac {n}{n-k}}}{\frac {n^{n}e^{-k}}{\left(n-k\right)^{n-k}k!}}p^{k}(1-p)^{n-k}.\end{aligned}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/db8039b02df92fe7f77a4d5f0e52e9ec501511f2)
Letting
and
:
![{\displaystyle {\begin{aligned}{n \choose k}p^{k}(1-p)^{n-k}&\simeq {\frac {n^{n}\,p^{k}(1-p)^{n-k}e^{-k}}{\left(n-k\right)^{n-k}k!}}\\&={\frac {n^{n}\left({\frac {\lambda }{n}}\right)^{k}\left(1-{\frac {\lambda }{n}}\right)^{n-k}e^{-k}}{n^{n-k}\left(1-{\frac {k}{n}}\right)^{n-k}k!}}\\&={\frac {\lambda ^{k}\left(1-{\frac {\lambda }{n}}\right)^{n-k}e^{-k}}{\left(1-{\frac {k}{n}}\right)^{n-k}k!}}\\&\simeq {\frac {\lambda ^{k}\left(1-{\frac {\lambda }{n}}\right)^{n}e^{-k}}{\left(1-{\frac {k}{n}}\right)^{n}k!}}.\end{aligned}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/ad205bebf4f9a1c824eacf8ca77990deca99b145)
As
,
so:
![{\displaystyle {\begin{aligned}{n \choose k}p^{k}(1-p)^{n-k}&\simeq {\frac {\lambda ^{k}e^{-\lambda }e^{-k}}{e^{-k}k!}}\\&={\frac {\lambda ^{k}e^{-\lambda }}{k!}}\end{aligned}}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/66670b4d6e131ad53d471ac4653e1285c9d4e517)
Ordinary generating functions
[edit]
It is also possible to demonstrate the theorem through the use of ordinary generating functions of the binomial distribution:
![{\displaystyle G_{\operatorname {bin} }(x;p,N)\equiv \sum _{k=0}^{N}\left[{\binom {N}{k}}p^{k}(1-p)^{N-k}\right]x^{k}={\Big [}1+(x-1)p{\Big ]}^{N}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/84f0051a42e4b4e3ad464aa8519f814360e3697c)
by virtue of the binomial theorem. Taking the limit
while keeping the product
constant, it can be seen:
![{\displaystyle \lim _{N\rightarrow \infty }G_{\operatorname {bin} }(x;p,N)=\lim _{N\rightarrow \infty }\left[1+{\frac {\lambda (x-1)}{N}}\right]^{N}=\mathrm {e} ^{\lambda (x-1)}=\sum _{k=0}^{\infty }\left[{\frac {\mathrm {e} ^{-\lambda }\lambda ^{k}}{k!}}\right]x^{k}}](https://wikimedia.org/api/rest_v1/media/math/render/svg/20230fc7a78091820f40495f377f27f4e36bb848)
which is the OGF for the Poisson distribution. (The second equality holds due to the definition of the exponential function.)